The Influences of Merger and Acquisition on Firm Performance and Shareholder Wealth: the Evaluation of the US Bidder Firms - He, Jingru (2014)
Mergers and acquisitions (M&A) has been widely considered as an efficient strategy to realize the managerial goal, which is maximizing the shareholder wealth. Meanwhile, managers choose to engage in M&A deals in order to maintain their controlling power. The M&A transaction was first developed in the US market, which constitutes as a dynamic market that most studies have been interested in. There exists consensus provided by previous empirical studies that M&A can enhance the target firms’ shareholder wealth. However, varied results have been reported for the bidders. Some reveal that bidders can raise positive gains from M&A deals, while other researchers argue there is zero or even negative returns to bidders.